Interfacing an EPC Gen 2 UHF RFID reader to a wireless backbone using GSM - Vizcaya, Leah I. (2008.)
This project interfaces a wireless backbone to SkyeTek SkyeModule M9, an EPC Gen 2 UHF RFID reader. The wireless backbone consists of a microcontroller board connected to a GSM module, parse the input, send it to the M9, obtain M9 feedback, and send the reply back to the user who initiated the command. The project used BenQ M23 GSM Module, a tri-band GSM900 cellular engine.
Undergraduate Student Project (B.S. ECE)--University of the Philippines, Diliman.
Keywords: Radio frequency identification systems; Global system for mobile communications; RFID reader; GSM; SkyeTek SkyeModule M9.